Queratoses actínias disseminadas de membros superiores: comparação da terapia fotodinâmica com ácido aminolevulínico 15%¨e metil aminolevulínico 15 % através do protótico kerato PDT - Oliveira, Elisangela Ramos de [UNESP] (2014)
Skin cancer is the most common type of cancer in Brazil, accounting for 25 % of all cancers registered in actinic keratoses country (AKs) are common precancerous lesions , with an estimated 60% of patients over the age incidence 60 years, AKs can progress to squamous cell carcinoma (SCC ) is a type of aggressive skin cancer melanoma, may be responsible for 34 % of deaths from skin cancer in the world. Photodynamic therapy (PDT) for AK with 5 - aminolevulinic acid ( ALA ) or methyl aminolevulinate ( Methyl- ALA ) is an accepted treatment option for this disease , due to its effectiveness and excellent cosmetic results . The aim of this study was to evaluate and compare the pain reported by the patients during the treatment of PDT using the medicine Methyl- ALA and ALA a15 %. AK 40 patients were selected for the upper limbs, the division performed and two groups of 20 patients, the drug administered group I and group II ALA administered -ALA methyl , then the remaining members were occluded for 3 hours, after curative was removed and held the lighting in the area for 40 minutes with a fluence of 36 J / em 2 , the prototype Kerato PDT -based LED emitters . During the lighting and every 5 minutes a numerical visual scale (NVS) was applied to measure referred pain . The lesions were imaged and quantified before and 30 days after treatment. Data were statistically analyzed by Student's paired t-test, Friedman test and Tukey 's t testo The results showed no statistically significant difference between the two groups, and that both drugs used were effective in the treatment of AKs . Comparing the pain reported by the patients during treatment , there was no statistical difference between the female and the male , nor between the two groups, although for males the pain scale was statistically higher when used Methyl- ALA . We conclude that both drugs may be indicated for the treatment of AKs scattered in the upper limb, and more studies focused ...